(untitled) (CIPEEX, 2025)
This study argues that, in the personal service of a defendant regarding a pronúncia (committal) order or a conviction in jury proceedings, the failure to present a notice of appeal at the time of service or to ask about the defendant’s intention to appeal does not nullify the act of service. It is a descriptive-analytical, doctrinal inquiry reviewing criminal-procedure scholarship and pertinent case law to delineate the content and purpose of personal service. Methodologically, it identifies statutory bases and ratios decidendi holding that unequivocal notice to the defendant suffices for valid service, regardless of additional formalities, provided adversarial principles and the right to a defense are preserved. The findings indicate that service remains valid when it performs its informative function and the defendant has means and time to exercise the right to appeal; requiring a contemporaneous notice of appeal or an express inquiry into the intention to appeal is not a condition of validity. It concludes that declarations of nullity must follow the no-harm principle, avoiding sterile formalism and promoting efficiency in criminal proceedings.